Correlates of cognitive functioning in independent elderly patients discharged home from the emergency department after a minor injury. (25th April 2016) - Ouellet, Marie-Christine; Sirois, Marie-Josée; Beaulieu-Bonneau, Simon; Gagné, Marie-Ève; Morin, Jacques; Perry, Jeffrey; Daoust, Raoul; Wilding, Laura; Provencher, Véronique; Camden, Stéphanie; Allain-Boulé, Nadine; Émond, Marcel
ABSTRACT: Background: The objective of this study was to explore correlates of cognitive functioning of older adults visiting the emergency department (ED) after a minor injury. Methods: These results are derived from a large prospective study in three Canadian EDs. Participants were aged ≥ 65 years and independent in basic activities of daily living, visiting the ED for minor injuries and discharged home within 48 hours (those with known dementia, confusion, and delirium were excluded). They completed the Montreal Cognitive Assessment (MoCA). Potential correlates included sociodemographic and injury variables, and measures of psychological and physical health, social support, mobility, falls, and functional status. Results: Multivariate analyses revealed that male sex, age ≥ 85 years, higher depression scores, slower walking speed, and self-reported memory problems were significantly associated with lower baseline MoCA scores. Conclusions: These characteristics could help ED professionals identify patients who might need additional cognitive evaluations or follow-ups after their passage through the ED. Obtaining information on these characteristics is potentially feasible in the ED context and could help professionals alter favorably elderly's trajectory of care. Since a significant proportion of elderly patients consulting at an ED have cognitive impairment, the ED is an opportunity to prevent functional and cognitive decline.